Principles of forest types classification and forest management planning methods of the Czech Republic and their implementation for Ukrainian Carpathians - Holusha, O.; Parpan, V. (Науково-виробниче видання “Лісовий журнал”, 2011)
Analysis of the Czech experience gives a chance to implement their principles of the forest type classification for the Ukrainian Carpathians forests. Forestry action planning within forestry complexes is possible for 18–20 groups of forest types. The introduction of this planning system would significantly increase the area of managed forests in the region.